The Influence of Parental Attachment on Charley’s Personality Development in Mitch Albom’s For One More Day - Cristyvilda Priskila; Ratna Asmarani (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
This research thesis discusses the influence of different attachment patterns on the personality development of Charley Benetto in Mitch Albom's For One More Day. The objectives of this research are to identify Charley’s patterns of attachment to his parents, to analyze how insecure attachment influences his personality, and to analyze how secure attachment contributes to his personality development. This research thesis uses a psychological approach, employing John Bowlby’s Attachment Theory and supported by Elizabeth Hurlock’s Personality Development Theory. This research thesis employs a library research method. The primary data source is For One More Day, while secondary sources include scholarly books and journals related to attachment and personality development. The findings of this research thesis indicate that Charley’s insecure attachment to his father causes him to constantly seek his father’s approval, leading him to neglect his mother's love and make choices he regrets. In contrast, his secure attachment with his mother helps him to be confident, able to confront problems, develop emotional regulation, rebuild his broken relationships, and break free from his insecure attachment. These personality changes occur due to a change in self-perception, motivation driven by a deep internal desire to change, and a change in crucial individuals.